The Impact of Minimum Wage Increases on Unemployment in the V4 Countries: Assessing the Recommendations of the European Commission - Tkáčová, Andrea
Identifikovaanie vplyvu Kaitzovho indexu a niekoľkých ďalších vybraných premenných na nezamestnanosť v krajinách V4.